ASSESSMENT OF ULTRASOUND FINDINGS IN RENAL TRANSPLANT RECIPIENTS DURING THE POSTOPERATIVE PERIOD - Norkuziev, Sherali Safaralievich; Kurbanov Obid Makhsudovich; Muminov Javokhir Asliddinovich; Ismatov Tuichiboy Akhrorkulovich; Norkabilov Alisher Norbekovich; Olimov Ismoilkhon Zhamolkhon ugli; Mamatmurodov Anvar Abdusaidovich (Scholar Express Journals, 2025)
This study is devoted to the analysis of morphometric and hemodynamic changes in the renal graft in the post-transplant period using ultrasound diagnostic methods. The paper presents data on 53 patients (31 men and 22 women) who underwent kidney transplantation, who underwent ultrasound examination on the first day after surgery and 3 months later. Ultrasound diagnostics was performed using Mindray Consona N9 (ZST, Zone Sonography Platform). The graft volume, parenchyma thickness, resistance index (IR) of the renal artery and renal vein patency were taken into account. The study allowed us to evaluate changes in graft volumes, parenchyma thickness, as well as renal artery resistance and venous blood flow, which made it possible to identify the dynamics of recovery and predict possible complications.
Keywords: transplant morphometry; kidney transplantation; ultrasound diagnostics